Secas causam mudanças na fenologia reprodutiva de Syagrus romanzoffiana, mas não alteram a predação de suas sementes - Pedroso, Pedro Maurício (Universidade Federal de São Carlos, 2021)
The Atlantic Forest is a biodiversity hotspot and currently occupies a small fraction of its original area. In addition to the edge effects caused by habitat fragmentation, its plant and animal species also face the effects of climate change. Such changes can affect climate variations and cause more frequent extreme events, such as droughts. Plants and animals respond to abiotic variables and such responses are important to understand the effects of climate change on organisms and their interactions. Palm trees are an important element within the Atlantic Forest, mainly because they produce fruit during the dry season of the year when there is less supply of resources for fruit-eating animals. Plant-animal interactions can be beneficial to plants, such as seed dispersal, or negative, such as seed predation. Thus, understanding the factors that somehow impact the reproduction of plants that provide resources for other organisms is essential, since changes in reproductive characteristics of an organism can be reflected for other species, such as its predators. In this work we evaluated whether droughts alter the reproductive phenology of Syagrus romanzoffiana, a key species in the Atlantic Forest, and whether the possible alterations have cascading consequences for animals that consume its seeds. The main results indicate that drought increases the number of bunches of immature fruits, but reduces the number of bunches of flowers and ripe fruits. Droughts can also delay or advance the time of occurrence of these structures. However, such changes do not reflect differences in predation rates of Syagrus romanzoffiana, whose main predator (beetle) is not satiated by increased seed production, unlike the vertebrate predator, squirrels. Thus, despite the changes caused by drought in the reproductive phenology of S. romanzoffiana, seed predators are not affected.
Droughts change the reproductive phenology of Syagrus romanzoffiana, but do not alter seed predation
Keywords: Mata Atlântica; Mudança climática; Secas; Saciação de predadores; El Niño; Atlantic forest; Climate change; Droughts; ENSO; Predator satiation; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS